THE HAGARISM THEORY OF MICHAEL COOK: THE QUR’AN AND HADITH IN THE PERSPECTIVE OF RELIGIOUS SYNCRETISM - Pulungan, Nur Hamidah; Adhli, Aulya; Adnir, Farid; Masuwd, Mowafg Abrahem (LP2M Ma'had Aly Hasyim Asy'ari Pesantren Tebuireng, 2025)
The Hagarism theory developed by Michael Cook and Patricia Crone claims that Islam is the result of assimilation from Jewish, Christian, and pre-Islamic Arab cultural traditions. The Prophet Muhammad is accused of being the founder of a reform movement inspired by Judaism, which He and His followers were initially seen as part of a broader monotheistic tradition, before eventually formin a separate religious identity calling itself Muslims. This study aims to examine the Hagarism theory from the perspective of religious syncretism to assess the claim that the Qur'an and Hadith are products of the fusion of previous religions. This research employs a critical analysis method by reviewing the primary sources used by Cook and Crone and comparing them with Islamic historiography. The approach applied includes a literature review of orientalist texts and counterarguments from Muslim scholars. The findings indicate that the Hagarism theory has methodological weaknesses, as it relies on non-Muslim sources while disregarding Islamic traditions. The syncretic approach used in this theory also tends to overlook the originality of Islamic teachings. This study emphasizes the importance of a more objective academic approach in orientalist studies of Islam.[Teori Hagarisme yang dikembangkan oleh Michael Cook dan Patricia Crone mengklaim bahwa Islam merupakan hasil asimilasi dari tradisi budaya Yahudi, Kristen, dan Arab pra-Islam. Nabi Muhammad dituduh sebagai pendiri gerakan reformasi yang terinspirasi oleh Yudaisme, di mana beliau dan para pengikutnya awalnya dipandang sebagai bagian dari tradisi monoteistik yang lebih luas, sebelum akhirnya membentuk identitas keagamaan yang terpisah dengan menyebut diri mereka sebagai Muslim. Penelitian ini bertujuan untuk mengkaji teori Hagarisme dari perspektif sinkretisme agama guna menilai klaim bahwa al-Qur’an dan Hadis merupakan produk dari peleburan agama-agama sebelumnya. Penelitian ini menggunakan metode analisis kritis dengan menelaah sumber-sumber primer yang digunakan oleh Cook dan Crone serta membandingkannya dengan historiografi Islam. Pendekatan yang digunakan mencakup telaah pustaka terhadap teks-teks orientalis dan tanggapan dari para sarjana Muslim. Temuan penelitian menunjukkan bahwa teori Hagarisme memiliki kelemahan metodologis karena bergantung pada sumber-sumber non-Muslim dan mengabaikan tradisi Islam. Pendekatan sinkretis yang digunakan dalam teori ini juga cenderung mengesampingkan orisinalitas ajaran Islam. Penelitian ini menekankan pentingnya pendekatan akademik yang lebih objektif dalam studi orientalis terhadap Islam.]